A Pencil in Spinal Canal-penetrating Injury–Endoscopic Management - Vivek Agrawal; Kailash Rathod; Ranjit Rangnekar (Indian Journal of Neurosurgery)
Penetrating spinal trauma is a rare event and mostly occurs as a result of assault or accident. There is no specific management protocol about such injuries. We are reporting a case of spinal trauma in a child of 6 years, who encountered a penetrating injury to the lower back when he fell over a sharp pencil. It resulted in a penetrating wound in the lower back with half of the broken pencil fragment lodged deep into the wound. There was a watery discharge from the wound with severe backache and radiating pain in both lower limbs. On clinical examination, motor power of both lower limbs was 5/5 (Medical Research Council [MRC] grade) with intact sensation and severely restricted straight leg raise (SLR). Imaging revealed a large fragment of pencil lodged in the spinal canal at L4 vertebral level. Surgical removal of foreign bodies and dura repair was done with endoscope and without laminectomy. The backache and lower limb pain relieved completely with healing of puncture site. In this case, the endoscopic technique enabled us to direct visualize penetration tract, injured structures, removal of foreign bodies and hematoma with repair of dura and without doing a destabilizing bone cutting and tissue damage.